Family education: Instilling career expectations for woman - Prasetia, Agung Tri; Yunus, Ahmad Rozelan; Nirwana, Herman; Afdal, Afdal; Syukur, Yarmis; Iswari, Mega; Fikri, Miftahul (Journal of Education and Learning (EduLearn), 2024)
Because women in Indonesian society gain more experience in the family, one of which is education instilled through family gender culture, women's career aspirations are believed to have their own characteristics. In today's society, the current condition of female students' career expectations is apprehensive. Most of the female students do not have any professional characteristics, such as career aspirations. This research involving 109 female students from various cultural contexts will divide their findings into two categories: patriarchal family education and matriarchal family education. The main objective of this research is to investigate the career expectations of female students in relation to patriarchal and matriarchal family education, and to compare the two household categories. As a result, the majority of female students from societies that place a patriarchal emphasis on gender have expectations of career self-efficacy, whereas those from societies that place a matriarchal emphasis on gender have expectations of outcomes. Parametric analysis of variance (ANOVA) test was used for comparative analysis. The test results show F = 75.011 for career expectations on self-efficacy and F = 145.467 for outcome expectation (OE). 0.000 is a significant value for both variations.